Out-standing! Om Dansk Tennis Club og tennisspilleren Leif Rovsing - Kural, René (Forum for Idræt, 2013)
Out-standing! Danish Tennis Club and the Tennis Player Leif Rovsing On April 13, 1917 the Danish newspaper B.T. published an article about the nationally renowned Danish tennis player, Leif Rovsing, who was planning to build a magnificent tennis hall. Personally funding the project, he referred to the tennis hall as a ‘World-Sports-Establishment’ to be built on land he had found close to Copenhagen. On May 5, 1917 the Danish Football Association (DBU) excluded Rovsing from all clubs under their auspices and banned him from participating in all Danish tournaments due to “presumed homosexuality”. This was the starting point for Rovsing to realise the dream he had described in B.T. In cooperation with architect Henry Madsen he built the out-standing tennis hall, Dansk Tennis Club. From an architectural point of view, the 43,5 m long and 23,5 m wide tennis hall is an original piece of sports architecture worldwide, with its smallmuntined windows, providing the hall with an intake of daylight, which sheds a soft parallel light over the courts without blinding the players. The hall also came into being with a gentleman’s study, plush sofas, china over the doors, and wall decorations from Egypt and Bali. It is these unexpected juxtapositions that made Dansk Tennis Club so unusual at the time – and to this day.